2020
DOI: 10.1093/rheumatology/keaa858
|View full text |Cite
|
Sign up to set email alerts
|

Real-world single centre use of JAK inhibitors across the rheumatoid arthritis pathway

Abstract: Objectives To evaluate real-world efficacy of approved JAK inhibitors (JAKi) tofacitinib and baricitinib in a large, single-centre cohort of RA patients across the treatment pathway, including those refractory to multiple biologic drugs. Methods All RA patients, treated with tofacitinib (from time of compassionate access scheme) or baricitinib since approval in 2017 had DAS28-CRP scores and components recorded at baseline, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
10
18
0
Order By: Relevance
“…This study showed that baricitinib provides remission or low disease activity and pain relief, even in Patients included in the ORBIT-RA study were predominantly older females with moderate to highly active RA before starting baricitinib treatment. Clinical and sociodemographic characteristics of these patients were reasonably aligned with those of previous observational studies conducted in Spain, Italy, and the UK (18)(19)(20)(21) in terms of gender, age, years of disease, seropositivity status, comorbidities, and disease activity scores (DAS28-ESR, SDAI and CDAI). Our study showed baseline moderate levels of disease activity scores (DAS28ESR 4.3 ± 1.1, SDAI 10.9 ± 10.3 and CDAI 23 ± 10 like other observational studies (18)(19)(20)(21) and lower than those of the clinical trials with baricitinib.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This study showed that baricitinib provides remission or low disease activity and pain relief, even in Patients included in the ORBIT-RA study were predominantly older females with moderate to highly active RA before starting baricitinib treatment. Clinical and sociodemographic characteristics of these patients were reasonably aligned with those of previous observational studies conducted in Spain, Italy, and the UK (18)(19)(20)(21) in terms of gender, age, years of disease, seropositivity status, comorbidities, and disease activity scores (DAS28-ESR, SDAI and CDAI). Our study showed baseline moderate levels of disease activity scores (DAS28ESR 4.3 ± 1.1, SDAI 10.9 ± 10.3 and CDAI 23 ± 10 like other observational studies (18)(19)(20)(21) and lower than those of the clinical trials with baricitinib.…”
Section: Discussionsupporting
confidence: 77%
“…Clinical and sociodemographic characteristics of these patients were reasonably aligned with those of previous observational studies conducted in Spain, Italy, and the UK (18)(19)(20)(21) in terms of gender, age, years of disease, seropositivity status, comorbidities, and disease activity scores (DAS28-ESR, SDAI and CDAI). Our study showed baseline moderate levels of disease activity scores (DAS28ESR 4.3 ± 1.1, SDAI 10.9 ± 10.3 and CDAI 23 ± 10 like other observational studies (18)(19)(20)(21) and lower than those of the clinical trials with baricitinib. In the RA-BEAM study, the DAS28-ESR was 6.4 ± 1.0 and SDAI 40 ± 13 (14).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Another concern is whether the number or mode of action of prior bDMARDs or JAKi may affect the drug retention of JAKi. Although improvement in disease activity was greatest in the bDMARDs-naïve group, both BAR and TOF were effective in patients refractory to multiple bDMARDs 38 . In addition, prior use of bDMARDs did not affect the clinical efficacy of BAR 39 ; the clinical efficacy of BAR was similar regardless of previous multiple bDMARD use 40 .…”
Section: Discussionmentioning
confidence: 88%